Clinicopathologic features, tumor immune microenvironment and genomic landscape of EBV-related and EBV-unrelated poorly differentiated nonkeratinizing squamous cell carcinoma of the thymus. (May 2023) - Zhang, Yi-Jun; Xiong, Si-Ping; Yang, Yuan-Zhong; Fu, Sha; Wang, Tong-Min; Suster, David I.; Jiang, Gui-Yang; Zhang, Xiao-Fang; Xiang, Jin; Wu, Yan-Xia; Zhang, Wen-Li; Cao, Yun; et al.
Highlights: EBV-related poorly differentiated nonkeratinizing squamous cell carcinoma (PDNKSCC) of the thymus had significantly higher PD-L1 + tumor cells and PD-L1 + and CD8 + immune cells than EBV-unrelated PDNKSCC. EBV-related PDNKSCC of the thymus has a significantly higher level of tumor mutation burden (TMB), more recurrently mutant genes and unique recurrently altered chromosomal regions. A new prognostic group based on EBV status and growth patterns showed a significant association with patients' OS and PFS. EBV-related PDNKSCC of the thymus, especially the Group 1 defined in this study, could be a candidate for immunotherapy. Abstract: Objectives: Knowledge regarding thymic EBV-related poorly differentiated nonkeratinizing squamous cell carcinoma (PDNKSCC), also known as lymphoepithelial carcinoma (LEC), is extremely limited due to its rarity. Materials and Methods: This multi-institutional study enrolled 85 patients with thymic PDNKSCC. DNA in situ hybridization was performed to evaluate the EBV status of all 85 cases. Immunohistochemistry and next generation sequencing were performed to compare the differences in the clinicopathological and molecular features between EBV-related and EBV-unrelated PDNKSCC. Tumor-infiltrating lymphocytes (TILs) were also analyzed by these methods. Results: The 85 cases were classified into 27 EBV-related PDNKSCCs (31.8 %) and 58 EBV-unrelated PDNKSCCs (68.2 %) according to the EBV status, and 35 Lymphoepithelioma pattern (LP) (41.2 %) and 50 desmoplastic pattern (DP) (58.8 %) according to the histological characteristics. Compared to the EBV-unrelated PDNKSCC, EBV-related PDNKSCC showed a younger patient predominance and more commonly displayed a LP subtype. Additionally, LP-type cases were divided into two groups: Group 1 (EBV-related, 20/85) and Group 2 (EBV-unrelated, 15/85); the DP-type cases were divided into Group 3 (EBV-unrelated, 43/85) and Group 4 (EBV-related, 7/85). The four Groups showed a significant association with patients' OS and PFS. EBV-related PDNKSCC had significantly higher PD-L1 + tumor cells (TCs) and PD-L1 + and CD8 + immune cells (ICs) than EBV-unrelated PDNKSCC. The tumor microenvironment immune type (TMIT) I (PDL1-Tumor+/CD8-High) was more common in EBV-related PDNKSCC, especially in Group 1(LP and EBV related) with more than 90 % cases belonged to TMIT I. Molecular analysis demonstrated that EBV-related PDNKSCC had a significantly higher tumour mutational burden and frequency of somatic mutations than EBV-unrelated cases. Conclusions: EBV-related PDNKSCC, especially the Group 1, could be a candidate for immunotherapy and EBV positivity may provide an indication for the selection of targeted therapy due to their high tumour mutational burden.